THE ACCRUALS QUALITY AND THE ESTIMATED FUTURE PERFORMANCE - Muljanto Siladjaja (Management Research Studies Journal, 2020)
This previous empirical research has shown out, that the usage of accruals had the contribution negatively on investor’s perception, this current research has shown that the discretionary accruals quality had a positive contribution, which paves the way for investors to predict the future performance by concerning on the effect of dividend’s phenomenon. By developing out the measurement of the future prospect, this research has used the future market value as a new indicator, where the accounting information has a significant effect on an investment decision. This moderated multiple regression has used the dividend policy, where played a critical role in signaling communication, Thus, The causal research has the samples, that amounted 154 of the listed companies in the industrial manufacturing sector for the period 2015 until 2017. The result indicated that the discretionary accruals quality had given a practical guideline for the investor to estimate the future return with high accuracy. This dividend policy has minimized the pattern of opportunistic behavior in providing a misleading bias in the performance reporting when the dividend has strengthened the discretionary accruals quality positively on the future market value. By developing a mapping with the decision model, combined with Bayes Theorema, empirical research provides a brief illustration, pointed out the high financial statements quality implies the game theory. This research recommended that this dividend policy can be used as a mandatory obligation, and the regulators must issue public policies, which provide a push to management in implementing high accounting information quality.